Konsep Pendidikan Berbasis Multikultural ala Ki Hadjar Dewantara - Mukodi Mukodi (Jurnal Penelitian Pendidikan, 2012)
Abstract:There are two points in this research. First, there are lot of violence phenomena and the strainedsituation between the members of religious community in the society recently. Second, it has not foundthe way to solve the conflicts which is relevant to the Indonesians character. Related to the problems,the results of this study show that; 1) through multicultural teaching and learning method, theunique of human beings, such as the differences of religion or belief, race, culture, sex, physical aspectsand peoples’ economic status can be placed on the same level.2) the multicultural educational conceptof education in three centers of education by Ki Hajar Dewantara as one of the alternativeapplication methods. Trough familial education, the parents teach their children for understandingthe importance of having equal right among the ones who have different ethnic group, race, religion,belief, culture, social strata, and humanism values. At school, the teachers and academic staffs canteach the multicultural values of education which are systematic, academic, and controlled. In thesociety, the citizen or the members of the society can implement the feeling of awareness in the real life,related to the importance of seeing the differences of people without differencing the religion, belief,culture, sex, physical aspects and peoples’ social status.